Disgusting or delicious? Examining attitudinal ambivalence towards entomophagy among Danish consumers - (:unkn) unknown (Elsevier, 2020)
Current meat consumption habits will need to change, especially those of Western consumers. The level of meat consumption is unsustainable, and a recent study estimates a necessary reduction of 90% of the current intake. Insects are a promising alternative to existing protein sources, but previous literature has emphasised the initial level of disgust displayed towards insects as a food option. The overall aim of this paper is to understand the attitude of consumers towards eating insects, also termed entomophagy, in order to outline the barriers that prevent adoption and provide insights in order to overcome these. Data were collected through an online questionnaire with a representative sample of Danish consumers (n = 975). Several constructs from the literature were measured: food neophobia, disgust, intention to try and intention to eat regularly. In addition, a new attitude scale was used, that specifically measures the attitude towards entomophagy. A discrete choice experiment was a part of the questionnaire. Using LatentGold 5.1 a segmentation analysis based on the choice experiment was conducted. The influences of intention were analysed using hierarchical regression in SPSS 25. Results of the choice experiment indicate that different segments of consumers of entomophagy exist, and that different segments are interested in different types of insects. Younger consumers and males are more positive towards entomophagy in general and the insect options in the choice experiment. Results of the regression analysis indicate that the attitude toward eating insects is multidimensional and that there seem to be indications of attitude ambivalence in all segments. The interest in entomophagy is important, as it will be a key factor in overcoming the barrier of disgust and turning insects into an acceptable food choice in the Western world.
Keywords: entomophagy; consumer behaviour; attitude ambivalence; choice experiment; food choice; attitudes; food; consumers; food habits; nutrition; behaviour; edible insects; nutritional behaviour; opinions; fi=Markkinointi|en=Marketing|